Financial Sustainability - Game Theory Analysis of Options Approach for a Czech Bank - Karel Janda; Petr Marek (ZBW - Leibniz Information Centre for Economics, 2022)
This paper applies a model of bank run based on game theory analysis of options to the real world case of the Czech retail bank Air Bank a. s. We discuss the main factors affecting the susceptibility of Czech banks to bank run. We estimate the equity value which triggers bank run for Air Banks a. s. clients. We also simulate a possible bank run, using a liquidity stress test, which is similar to stress tests used by some European supervisory authorities. We provide alternative estimates of critical value of bank's equity after the attainment of which depositors withdraw their deposits and by doing so trigger a bank run.
Keywords: C72; G01; G21; 330; Bank run; liquidity; game theory; option pricing